IRINA ANTONOVNA KOROLKOVA – ONE OF THE FOUNDERS PEDIATRIC UROLOGICAL SERVICE IN MOSCOW REGION - V. V. Dutov (Вестник урологии, 2016)
In March 2016 the urological clinic of the Moscow Regional Research and Clinical Institute named after M.F. Vladimirskiy is 85 years old. The article presents a biography Korolkova Irina Antonovna, the activity of which was for many years closely associated with the work of the clinic.